Protective efficacy of rutin against acrylamide-induced oxidative stress, biochemical alterations and histopathological lesions in rats. Issue 1 (26th January 2022) - Uthra, Chhavi; Reshi, Mohd Salim; Jaswal, Amita; Yadav, Deepa; Shrivastava, Sadhana; Sinha, Neelu; Shukla, Sangeeta
Abstract: Acrylamide is a well-known neurotoxicant and carcinogen. Apart from industrial exposure, acrylamide is also found in different food products. The present study deals with in vivo experiment to test the protective effect of rutin against acrylamide induced toxicity in rats. The study was carried out on female rats with exposure of acrylamide at the dose of 38.27 mg/kg body weight, orally for 10 days followed by the therapy of rutin (05, 10, 20 and 40 mg/kg orally), for three consecutive days. All animals were sacrificed after 24 h of last treatment and various biochemical parameters in blood and tissue were investigated. Histopathology of liver, kidney and brain was also done. On administration of acrylamide for 10 days, neurotoxicity was observed in terms of decreased acetylcholinesterase activity and oxidative stress was observed in terms of increased lipid peroxidation, declined level of reduced glutathione, antioxidant enzymes (superoxide dismutase and catalase) in liver, kidney and brain. Acrylamide exposure increased the activities of serum transaminases, lipid profile, bilirubin, urea, uric acid and creatinine in serum indicating damage. Our experimental results conclude that rutin showed remarkable protection against oxidative DNA damage induced by acrylamide, which may be due to its antioxidant potential. Graphical Abstract: